Cover Picture: Disruption of Interactions between Hydrophobic Residues on Nonpolar Faces is a Key Determinant in Decreasing Hemolysis and Increasing Antimicrobial Activities of α‐Helical Amphipathic Peptides (ChemMedChem 10/2013). Issue 10 (2nd October 2013) - Son, Mieon; Lee, Yuri; Hwang, Heeyong; Hyun, Soonsil; Yu, Jaehoon
<x xml:space="preserve">Abstract</x> The front cover picture shows the modulation of hemolytic and antimicrobial activity of peptides through mutation. An amphipathic (green/black) α‐helical peptide composed of leucine and lysine residues was mutated (bright green) with a variety of amino acids to decrease the hemolytic activity (top) and improve the antimicrobial activity (bottom). Disruption of the segregated hydrophobicity by incorporation of neutral hydrophilic residues (green) gave rise to peptide derivatives with significantly decreased α‐helicity and hydrophobicity. One analogue (LK‐L8N) exhibited a greater than 8000‐fold decrease in hemolytic activity over the parent peptide and an 8‐fold improvement in antimicrobial activity against E. coli, giving a 64000‐fold increase in therapeutic index. This strategy is generally applicable in the design of selective antimicrobial peptides. For more details, see the Communication by Jaehoon Yu et al. on p. 1638 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>